A Fast Calculation Algorithm of Efficiency Map of Permanent Magnet Synchronous Machines Using Finite-element Method. Issue 1 (June 2021) - Li, Wei; Liang, Hongwei; Liu, Jun; Zhang, Wenhao
Abstract: A fast calculation algorithm of efficiency map of permanent magnet synchronous machines using finite-element (FE) method is proposed in this paper. The control strategy of the machine can be taken into account in the whole torque-speed operating region. The optimal current vector is obtained by using analytical calculations, where the material saturation is also included. By using the proposed method, only one run of time-stepping FE analysis is required below the rated speed. The calculation time of the efficiency map is much reduced compared to the conventional calculation method. An example is tested, and calculation results are given to verify the proposed method.